Technical Analysis and Stock Price Prediction? Evidence from Malaysian Stock Market - Lee, Kelvin Yong Ming; Mohamad, Jais; Bakri, Abdul Karim (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This study aims to examine the ability of technical analysis in predicting the stock price and generating profits. Two of the technical analysis indicators, which are (i) Variable Moving Average (VMA) and (ii) Elliot Wave Principle incorporated (Fibonacci numbers) are utilized in this study. In addition, this study also examines the relationship between the signals emitted by VMA and the stock returns. This study uses daily data of 569 stocks listed in the main market of Bursa Malaysia from 2005 to 2012. The empirical findings indicate that the VMA are useful technical indicator in analysing the medium capitalization stocks. This result is further supported using the sub-sample and out-of-sample test. Moreover, the signals emitted via VMA rules are found to be significant influencing the stock returns. Furthermore, the results also show that the Elliot Wave Principle (Fibonacci numbers) is found to be significant influencing the stock price movements of large capitalization stocks. The results of this study have a significant implication towards investors and technical analysts.